2021
DOI: 10.12669/pjms.37.3.3911
|View full text |Cite
|
Sign up to set email alerts
|

The reasons and countermeasures of Bladder Rupture caused by Transurethral Clot Evacuation

Abstract: Objective: Bladder rupture caused by transurethral clot evacuation is rare in clinic, but an emergency operation is indeed needed in the patient with bladder rupture. We analyzed the reasons of bladder rupture caused by transurethral clot evacuation and provided the countermeasures to guide clinical surgeon to prevent the iatrogenic damage of bladder. Method: We retrospectively reviewed the records of 287 patients in our hospital, who had bladder tamponade resulting from clots of blood for various reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…At present, the most commonly used method to remove bladder blood clots is endoscopic blood clot removal and manual bladder irrigation ( 4 , 11 ), however, there were some disadvantages, such as low suction efficiency and unclear vision. This method might cause bladder mucosal damage and bladder perforation, prolong the operation time and increase the risk of infection ( 12 , 13 ). One study reported that a tissue pulverizer could be used to remove bladder blood clots.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most commonly used method to remove bladder blood clots is endoscopic blood clot removal and manual bladder irrigation ( 4 , 11 ), however, there were some disadvantages, such as low suction efficiency and unclear vision. This method might cause bladder mucosal damage and bladder perforation, prolong the operation time and increase the risk of infection ( 12 , 13 ). One study reported that a tissue pulverizer could be used to remove bladder blood clots.…”
Section: Discussionmentioning
confidence: 99%
“…Among endoscopic procedures, authors have described direct Ellik suction [ 13 ] or variations of the technique, such as the use of a resectoscope or morcellation device to achieve a progressive reduction of clots and facilitate Ellik suction [ 4 , 14 , 15 ]. Nevertheless, the bladder distension that occurs during the procedure represents a risk factor for bladder rupture [ 13 ]. Other authors, in case of Ellik failure, have proposed continuous mechanical suction [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%